Computer simulation and data compilation of sputtering yield by hydrogen isotopes (1H+, 2D+, 3T+) and helium (4He+) ion impact from monatomic solids at normal incidence - 402041 Yamamura, Y.; Kazuho Sakaoka; Hiro Tawara (Nagoya, Japan : NIFS, 1995)
40